Outcome Harvesting. Understanding social change results in complex cir cumstances (outcomeharvesting.net, 2018)
This website is a source of applications, events and resources to supp ort the development of a community of practitioners of Outcome Harvest ing. BetterEvaluation is one of three sister sites of OutcomeHarvestin g.net